2001
DOI: 10.1002/1529-0131(200103)44:3<585::aid-anr107>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase and proinflammatory cytokine production by chondrocytes of human osteoarthritic cartilage: Associations with degenerative changes

Abstract: Objective.To examine by immunohistochemistry the relative distributions of 6 matrix metalloproteinases (MMPs 1, 2, 3, 8, 9, and 13) and the 2 proinflammatory cytokines interleukin-1␤ (IL-1␤) and tumor necrosis factor ␣ (TNF␣) in osteoarthritic (OA) cartilage compared with normal, age-matched articular cartilage.Methods. Articular cartilage samples were obtained from the tibial plateau of OA knees removed at arthroplasty and from normal, nonarthritic, knees obtained at autopsy. Specimens were promptly fixed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
194
0
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(221 citation statements)
references
References 21 publications
16
194
0
11
Order By: Relevance
“…Recently, chondrocytes in the superficial and medial zone in OA cartilage have been reported to be positive for IL-1␤ and TNF-␣ compared with normal cartilage using immunohistologic methods (32). We have also shown functional up-regulation of TNF-␣ and TNF-␣ convertase activity in human OA-and RA-affected cartilage compared with normal (33).…”
Section: Discussionsupporting
confidence: 49%
“…Recently, chondrocytes in the superficial and medial zone in OA cartilage have been reported to be positive for IL-1␤ and TNF-␣ compared with normal cartilage using immunohistologic methods (32). We have also shown functional up-regulation of TNF-␣ and TNF-␣ convertase activity in human OA-and RA-affected cartilage compared with normal (33).…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, we recently demonstrated that the combination of IL-1␣ and OSM was able to synergistically induce messenger RNA (mRNA) expression for all 3 collagenases in chondrocytes, with a concomitant increase in MT1-MMP expression (66). Increased MMP-1 expression has also been detected in rheumatoid synovium and cartilage (67) and in osteoarthritic cartilage (68). MMP-13 protein is present in the pannus-hard tissue junction in RA (69) and in osteoarthritic cartilage (68).…”
Section: Discussionmentioning
confidence: 99%
“…Increased MMP-1 expression has also been detected in rheumatoid synovium and cartilage (67) and in osteoarthritic cartilage (68). MMP-13 protein is present in the pannus-hard tissue junction in RA (69) and in osteoarthritic cartilage (68). However, type II collagen is the principal collagen in cartilage and is cleaved most efficiently by MMP-13 (25,63).…”
Section: Discussionmentioning
confidence: 99%
“…There is a consensus that these enzymes play a critical role in intrinsic chondrocyte-mediated degenerative changes of the cartilage matrix in OA. Proinflammatory cytokines such as interleukin-1 (IL-1) strongly stimulate the expression of MMPs by chondrocytes in arthritis (8).…”
mentioning
confidence: 99%